Overview Quality Of Work Life, Career Decision Making Difficulties And Readiness To Change In Generation Z Employees Who Do Career Hopping - Hotpascaman Simbolon (Jurnal Pendidikan, Sains Sosial, dan Agama, 2025)
This study aims for the reviewing the overview mapping gen z for career hopping and the correlation with several variables. The main quesionaire using the CAAS for career making difficulties, The TIS for turnover intention scale. The population of this study were agre from 18 – 30 for defining the gen z and having a career hopping for the past two years. This study were ethically established from KPIN (Konsorsium Psikologi ilmiah Nusasntara) ground. Total sample were 92 people with several varians were discussed below. The questionnaire were using several online method such as tiktok and whatsapp community. Results shows that all variables significantly toward turnover intention with significant p<0.01. In this article also using the sum of gen z and sex as control variables. Other main result were Readiness to change mediate the variable between QWL and Turnover intention with indirect contribution 0,095. Readiness to change also mediate CAAS toward Turnover intention partially with contribution 0.109. This paper may suggest as company gave attention to co worker gen z with highly dissatisfaction, uncomfort for making adaption decision and turnover record.